Tanggungjawab Pelaku Usaha dan Marketplace terhadap Pelanggaran Asas Itikad Baik dalam Transaksi E-commerce - Rizkinil Jusar; Palmawati Taher; Inge Dwivismiar (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2023)
E-commerce through the marketplace is basically the same as buying and selling in general, where an agreement is required between the seller and the buyer regarding the goods or services being traded and the price for the goods or services, but in E-Commerce as in general, the goods being traded in the marketplace cannot be seen directly so it is possible that sellers who do not have good faith will not provide true information about the goods they are buying and selling. This research was conducted using normative juridical research methods. Data collection techniques were carried out by means of a literature study and using a statutory, case and theoretical approach. The principle of faith is a principle that must be put forward in social life, in this case good faith must be carried out by the seller in order to provide more protection to buyers or consumers, so that there are no more complaints from consumers about defaults committed by business actors that the goods sent are not in accordance with what is expected promised. In order to prevent more consumer complaints about defaults by business actors, the marketplace will be responsible for 'setting up' the electronic system and 'managing' it so that it is reliable, safe and responsible. This is in accordance with the theory of responsibility which places more emphasis on the meaning of responsibility born from the provisions of laws and regulations so that the theory of responsibility is interpreted in the sense of liability, as a concept related to the legal obligations of a person being asked for their actions and can be subject to sanctions if they are contrary to law.